ANALISA TINGKAT STRES KERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SDM KOTA BIMA KOTA BIMA - Megasuciati Wardani (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
This research aims to determine and analyze the level of work stress of employees at the BIMA City Personnel and Human Resources Development Agency Office, Bima City. The type of research used is descriptive research. Location This research was carried out at the BIMA City Personnel and Human Resource Development Agency Office. The population in this study were all employees at the BIMA City Personnel and Human Resources Development Agency Office, Bima City, whose address was Raba, Bima City, totaling 40 people. From the population above, 40 employees will be sampled. From the results of respondents' answers, the value is in the interval 1001–1500 in the good category. The calculated t value in the one sample t test analysis is 10.87 which is greater than the t table value of 1.684. Thus, the hypothesis which states that it is estimated that the work stress of employees at the BIMA City Personnel and Human Resource Development Agency Office is lower than 40% can be accepted. The level of work stress for employees at the BIMA City Personnel and Human Resources Development Agency Office is still at a tolerable level.